2017
DOI: 10.1371/journal.pone.0178525
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory and antioxidant effects of melatonin on LPS-stimulated bovine mammary epithelial cells

Abstract: Mastitis is the most prevalent disease in dairy cattle worldwide and not only causes huge economic losses in the dairy industry but also threatens public health. To evaluate the therapeutic potential of melatonin in mastitis, we examined the ability of melatonin to protect bovine mammary epithelial cells (bMECs) from the harmful effects of lipopolysaccharide (LPS). We found that melatonin inhibited the LPS-binding protein–CD14–TLR4 signaling pathway in bMECs, which had opposing effects on pro-inflammatory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 58 publications
4
79
2
1
Order By: Relevance
“…As the proinflammatory actions of TLR4 are frequently also associated with NF‐κB activation and prooxidant effects, inhibitory actions of melatonin on TLR4 are of particular mechanistic interest for the understanding of reducing inflammation. This mode of action by melatonin was repeatedly demonstrated and sometimes shown to be associated with inhibitions of NF‐κB and of inflammasome activation as well as upregulation of Nrf2 . These findings were obtained in different organs and models, under various conditions, from endotoxemia, ischemia/reperfusion and other forms of brain injury to chemically induced inflammation.…”
Section: Downstream Factors Of Melatonin's Actions With Relevance Tomentioning
confidence: 79%
“…As the proinflammatory actions of TLR4 are frequently also associated with NF‐κB activation and prooxidant effects, inhibitory actions of melatonin on TLR4 are of particular mechanistic interest for the understanding of reducing inflammation. This mode of action by melatonin was repeatedly demonstrated and sometimes shown to be associated with inhibitions of NF‐κB and of inflammasome activation as well as upregulation of Nrf2 . These findings were obtained in different organs and models, under various conditions, from endotoxemia, ischemia/reperfusion and other forms of brain injury to chemically induced inflammation.…”
Section: Downstream Factors Of Melatonin's Actions With Relevance Tomentioning
confidence: 79%
“…A previous study showed that tumor necrosis factor (TNF-α), IL-1β, IL-8, and IL-6 mRNA expression increased significantly in bovine mammary epithelial cells under LPS treatment (Yu, Kubota, Okita, & Maeda, 2017). In addition to ER stress associated with immune responses, the activation of IkB kinase and nuclear factor-κB (NF-kB) led to proinflammatory cytokine production and cell death (Tam, Mercado, Hoffmann, & Niwa, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As activated in β cells exposed to smoking, caspase‐3 eventually executes apoptosis either by extrinsic or intrinsic pathway and plays a central role in the execution phase of β cell apoptosis. In addition to its chronobiotic activity, melatonin has anti‐inflammatory and antioxidative effects, ranging from the direct scavenging of ROS to the regulation of antioxidant enzymes, such as superoxide dismutase, catalase, and glutathione peroxidase . Also, melatonin can promote the expression of glucose transporter, glucose transporter type‐4, which can be inhibited by oxidative stress .…”
Section: Discussionmentioning
confidence: 99%